National consensus on oncoplastic breast conserving surgery in Turkey: position paper for the standardization of surgical practice - (:unkn) unknown (TURKISH SURGICAL ASSOC, 2020)
Objective: The algorithms that define most of the application of oncoplastic breast conserving surgery (OBCS) in breast cancer patients are not clearly defined. Therefore, a consensus survey was conducted between the leading and experienced breast surgeons and oncoplastic breast surgeons in Turkey on the controversial areas of oncoplastic breast surgery. Material and Methods: This consensus survey was carried out on-line through the Consensus software program (www.consensuss.com ) under the roof of Turkish Federation of National Societies for Breast Diseases (TFNSBD). After finalizing each proposition, web-based remote access consensus process was performed on the Likert scale using Delphi method with the Consensus (www.consensuss.com ) software program. Through the related software, an invitation was sent to 111 people who had at least 5 years of general surgery expertise in Turkey, and who devoted more than 50% of their daily clinical practice to the treatment and surgery of breast diseases. Results: Sixty-two out of 111 people accepted to participate in the panel and made an on-line evaluation. According to the consensus results; Lumpectomy area should be done by placing the clips on at least four walls of the cavity, if the margin of the tumor is clear in central tumors, the distance between the tumor and the nipple is not significantly important, oncoplastic techniques may be used in patients with locally advanced breast cancer after neoadjuvant chemotherapy, in patients who have macromastia with ductal carcinoma in situ or breast cancer, OBCS techniques can be performed, and OBCS should be evaluated in terms of breast aesthetics. After OBCS, re-excision can be performed at a re-do setting in cases with involved surgical margins. Conclusion: Our consensus results may provide a basis for the development of some standards in OBCS.
Keywords: Oncoplastic breast conserving surgery; standardization; consensus; THERAPEUTIC MAMMAPLASTY; REDUCTION MAMMAPLASTY; CANCER; MASTECTOMY; RECONSTRUCTION; RADIOTHERAPY; ASSOCIATION; MARGINS; VOLUME; SIZE